Teachers' perspectives on the relationship between secondary school departments of science and religious education: Independence or mutual enrichment? - Woolley, Mary; Bowie, Robert A.; Hulbert, Sabina; Thomas, Caroline; Riordan, John‐Paul; Revell, Lynn (Curriculum journal (London, England), 2024)
There is a gap in the research on the relationship between secondary school subject departments, particularly where, as in the case of science and religious education (RE), there is not the traditional relationship that may be seen in science and maths or across humanities subjects. More awareness of content taught in other departments is important for pupils' coherent experience of curriculum and schooling. This article reports on data from 10 focus groups with 50 participants from six universities, where student teachers of science and RE revealed a complex picture of relationships between the two departments in their placement schools. Furthermore, this article reports findings from a survey where 244 teachers and student teachers of science and RE shared their perspectives on the relationship between the two school departments. The measure was adapted from Barbour's typology, a classification describing the nature of the relationship between science and religion in a range of literature. The terms ‘conflict’, ‘independence’, ‘dialogue’, ‘collaboration’ and ‘integration’ were presented to teachers of both subjects. Little evidence was found of conflict between science and RE departments, but more ‘independence’ than ‘dialogue’ between the two departments was reported. In the light of these findings, the benefits of boundary crossing are explored alongside the role teachers should play in boundary crossing.